2021
DOI: 10.3390/cells10092190
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Sensitive and Folate-Receptor-Mediated Targeting of Cervical Cancer Cells for Photodynamic Therapy Using Nanophotosensitizers Composed of Chlorin e6-Conjugated β-Cyclodextrin via Diselenide Linkage

Abstract: The aim of this study was to fabricate a reactive oxygen species (ROS)-sensitive and folate-receptor-targeted nanophotosensitizer for the efficient photodynamic therapy (PDT) of cervical carcinoma cells. Chlorin e6 (Ce6) as a model photosensitizer was conjugated with succinyl β-cyclodextrin via selenocystamine linkages. Folic acid (FA)-poly(ethylene glycol) (PEG) (FA-PEG) conjugates were attached to these conjugates and then FA-PEG-succinyl β-cyclodextrin-selenocystamine-Ce6 (FAPEGbCDseseCe6) conjugates were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…For the singlet oxygen (SO) generation and PDT study, an expanded homogenous beam (SH Systems, Gwangju, Korea) was used as reported previously [ 42 ]. The cells or nanophotosensitizers were irradiated at 664 nm and the light density was 2.0 J/cm 2 [ 42 ]. The distance between the cells or nanophotosensitizer solutions from the LED panel was 40 cm.…”
Section: Methodsmentioning
confidence: 99%
“…For the singlet oxygen (SO) generation and PDT study, an expanded homogenous beam (SH Systems, Gwangju, Korea) was used as reported previously [ 42 ]. The cells or nanophotosensitizers were irradiated at 664 nm and the light density was 2.0 J/cm 2 [ 42 ]. The distance between the cells or nanophotosensitizer solutions from the LED panel was 40 cm.…”
Section: Methodsmentioning
confidence: 99%
“…A multifunctional nanocomplex for FR-targeted delivery of photosensitizer with ROS sensitivity was developed by Kim et al (2021 ) for eliciting PDT upon HeLa cells. For the purpose FA-PEG was conjugated with β-CD, which was further linked using diselenide to the photosensitizer chlorin e6 (Ce6) via dialysis method.…”
Section: Cyclodextrin Nanoparticles For Anticancer Applicationsmentioning
confidence: 99%
“…Apoptosis, autophagy and necrotic cell death are the common forms of cancer cell death induced by ROS ( 33 ). Several clinical treatments, such as photodynamic therapy (PDT), whose mechanism mainly induces ROS to destroy and kill cervical cancer cells ( 34 , 35 ).…”
Section: Radiotherapy In Cervical Cancer Treatment and The Occurrence...mentioning
confidence: 99%